Clinical correlates and prognostic values of pseudoinfarction in cardiac light-chain amyloidosis. Issue 5 (November 2016) - Zhao, Lei; Li, Jian; Tian, Zhuang; Fang, Quan
Abstract: Background: Pseudoinfarction is one of the most common electrocardiographic characteristics in cardiac light-chain (AL) amyloidosis. The aim of the present study was to analyze the prognostic significance of pseudoinfarction and define the relation between pseudoinfarction and clinical parameters in cardiac AL amyloidosis. Methods: A total 110 consecutive patients who presented with a diagnosis of cardiac AL amyloidosis and without a positive history of coronary disease between 2010 and 2014 were enrolled. Patients were divided into two groups according to the presence ( n  = 40) or absence ( n  = 70) of pseudoinfarction on electrocardiography (ECG). Clinical parameters including laboratory tests, echocardiography, and follow-up were collected and analyzed. Results: Patients with pseudoinfarction had higher N-terminal pro-brain natriuretic peptide levels (9131 pg/ml vs 4644 pg/ml, p  = 0.02) and a worse New York Heart Association (NYHA) function ( p  < 0.001). The pseudoinfarction group also had a larger left atrium size (44 mm vs 41 mm, p  = 0.03), a thicker ventricular wall (septum 14 mm vs 13 mm, p  = 0.005 and posterior wall 14 mm vs 13 mm, p  = 0.01), a lower left ventricular ejection fraction (50% vs 58%, p  = 0.013), and higher early-to-atrial transmitral flow velocity ratio ( p  = 0.001). Also, the pseudoinfarction group was closely associated with a lower voltage (70% vs 38.6%, p  = 0.002), poor precordial R wave progression (78.4% vs 43.9%, p  = 0.001), lower Sokolow–Lyon index (13 mm vs 9 mm, p  < 0.001), and lower voltage to mass ratio (0.521 vs 0.442, p  = 0.028) on the ECG. After a median follow-up of 39 months, Kaplan–Meier survival analysis showed that lifetime was significantly shorter in the pseudoinfarction group (median 4 months vs 17 months, p  < 0.001). By adopting the multivariate Cox proportional model, NYHA heart failure III to IV and the presence of pseudoinfarction remained the only two independent prognostic determinants with death hazard ratio of 3.16 and 1.9, respectively. Conclusions: The presence of pseudoinfarction on the ECG has a negative prognostic effect on AL patients with cardiac involvement.